PENGARUH PELAKSANAAN AUDIT INTERNAL TERHADAP PENERAPAN GOOD CORPORATE GOVERNANCE - Soedijatno, Karli; Esa Teddy S., Morena (Jurnal Riset Akuntansi dan Keuangan, 2013)
This study aims to find out how the implementation of internal audit, the application of the principles of Good Corporate Governance, and the influence of the implementation of internal audit on the application of the principles of Good Corporate Governance at SOEs headquartered in Bandung. The hypothesis of this research is the influence of the implementation of internal audit on the implementation of Good Corporate Governance.Hypothesis testing in this study using software SPSS 19.0 for windows. The research method used is associative method with quantitative approach. The data used is the primary data in the form of questionnaires distributed to respondents. Data collected amounted to 66 questionnaires from BUMN internal auditors headquartered in Bandung.The results of this study indicate that the implementation of internal audit on SOEs headquartered in Bandung has been implemented very well and the implementation and application of Good Corporate Governance principles in SOEs headquartered in Bandung has been implemented very well so that only need to be maintained implementation. While the influence of internal audit variables on the implementation of principles of Good Corporate Governance of 67.08%. Thus, the hypothesis proposed in this study is accepted, that is, internal audit has an effect on the implementation of Good Corporate Governance.